2001
DOI: 10.1093/neucas/7.4.303
|View full text |Cite
|
Sign up to set email alerts
|

The Right Hemisphere’s Role in Action Word Processing: a Double Case Study.

Abstract: Word category-specific deficits were investigated in two patients with right hemispheric lesions and hemiparesis affecting the left extremities. Words from three categories, action verbs, nouns with strong visual associations and nouns with both strong action and visual associations, were presented in a lexical decision task. The stimulus categories were matched for word length and frequency. In both patients, responses to action verbs were slowed and/or less accurate compared with the other word categories. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(21 citation statements)
references
References 0 publications
2
19
0
Order By: Relevance
“…The present results also replicate the finding reported earlier that right frontal lesions can impair the processing of action verbs more than that of visually-related nouns [32,45]. In the earlier studies, data obtained from patients with right-hemispheric lesions were contrasted with the performance of a control group matched for age and level of education.…”
Section: Comparison Of the Present Results With Earlier Findingssupporting
confidence: 91%
See 2 more Smart Citations
“…The present results also replicate the finding reported earlier that right frontal lesions can impair the processing of action verbs more than that of visually-related nouns [32,45]. In the earlier studies, data obtained from patients with right-hemispheric lesions were contrasted with the performance of a control group matched for age and level of education.…”
Section: Comparison Of the Present Results With Earlier Findingssupporting
confidence: 91%
“…Additional involvement of the parietal lobes was present in 11 patients, and perisylvian lesions including inferior parietal and superior temporal areas was seen in 8 patients. In an earlier study [32], we found that small lesions restricted to the right motor and premotor cortex and larger right-perisylvian lesions including motor, premotor and inferior prefrontal areas caused the same category-specific deficits in word processing. Therefore, we grouped these patients together here.…”
Section: Subjectsmentioning
confidence: 54%
See 1 more Smart Citation
“…Moreover, damage to the sensory and motor cortex disrupts linguistic processing. Neininger and Pulvermueller (2001) studied a patient with a minor lesion on the motor, premotor, and somatosensory areas associated with the hand in the right hemisphere. They discovered that the patient had slower and less accurate responses to action verbs compared with the other word categories.…”
Section: Nontraditional Brain Areas and Language Processingmentioning
confidence: 99%
“…Vice versa, action word processing may impact on specific motor mechanisms, with effects visible in behaviour and in electrophysiological brain recordings 2 Fischer & Zwaan, 2008;Glenberg & Kaschak, 2003;Ibanez et al, 2012;Pulvermü ller, Hauk, Nikulin, & Ilmoniemi, 2005;Rueschemeyer, Lindemann, van Elk, & Bekkering, 2009;Schomers & Pulvermü ller, 2016;Schomers, Kirilina, Weigand, Bajbouj, & Pulvermü ller, 2015;Shebani & Pulvermü ller, 2013). Fifth, and finally, movement disorders and clinical impairments to motor systems are associated with specific processing impairments or abnormalities for action-related words which call on action knowledge in the retrieval of their meaning (Bak & Chandran, 2012;Boulenger et al, 2008;Cardona et al, 2014;Cotelli et al, 2006;García & Ibañez, 2014;Grossman et al, 2008;Kemmerer, 2015;Neininger & Pulvermü ller, 2001Pulvermü ller et al, 2010). 3 Whilst the effects of motor damage on action word processing have been thoroughly documented in many populations with acquired brain damage or disease states, we here examine grounded cognition and action semantics through the lens of a very different type of movement disorder.…”
mentioning
confidence: 99%